Pengaruh Kultur Sekolah terhadap Kualitas Pendidikan di SMPS Yos Sudarso Jerebu'u - Bernadino Alexantro Rato; Dionisius Patrison Nono; Reynaldus Begu; Adrianus Gae; Josep Marianus Rewo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This article examines the influence of school culture on the quality of education at SMPS Yos Sudarso Jerebu'u, Ngada Regency. This study aims to analyze how the values embedded in school culture affect the teaching and learning process, the development of student character, and the relationships among students, teachers, and parents. A qualitative case-study approach was employed, with data collected through in-depth interviews, participatory observation, and document analysis of school activities and policies. The results show that a school culture emphasizing discipline, mutual cooperation, and a strong sense of responsibility plays an important role in creating a conducive learning atmosphere and motivating students to reach their full potential. In addition, active parental involvement and harmonious relationships between teachers and students strengthen the contribution of school culture to improving the quality of education. Leadership shown by the school principal and exemplary behavior of teachers are also found to be decisive factors in building and sustaining a positive school culture. Overall, this study confirms that a positive and inclusive school culture, supported by strong leadership and active family involvement, can become a key factor in creating quality education and supporting the holistic development of students at SMPS Yos Sudarso Jerebu'u.